Heterogeneity and Lobularity of Pancreatic Pathology in Type 1 Diabetes during the Prediabetic Phase. (August 2015) - Rodriguez-Calvo, Teresa; Suwandi, Jessica S.; Amirian, Natalie; Zapardiel-Gonzalo, Jose; Anquetil, Florence; Sabouri, Somayeh; von Herrath, Matthias G.
Type 1 diabetes (T1D) is an autoimmune disease in which insulin-producing beta cells are destroyed in the islets of Langerhans. One of its main pathological manifestations is the hyper-expression of Major Histocompatibility Complex I (MHC-I) by beta cells, which was first described over 3 decades ago yet its cause remains unknown. It might not only be a sign of beta cell dysfunction but could also render the cells susceptible to autoimmune destruction; for example, by islet-infiltrating CD8 T cells. In this report, we studied pancreas tissue from a 22-year-old non-diabetic male cadaveric organ donor who had been at high risk of developing T1D, in which autoantibodies against GAD and IA-2 were detected. Pancreas sections were analyzed for signs of inflammation. Multiple insulin-containing islets were identified, which hyper-expressed MHC-I. However, islet density and MHC-I expression exhibited a highly lobular and heterogeneous pattern even within the same section. In addition, many islets with high expression of MHC-I presented higher levels of CD8 T cell infiltration than normal islets. These results demonstrate the heterogeneity of human pathology that occurs early during the pre-diabetic, autoantibody positive phase, and should contribute to the understanding of human T1D.